Serum Iron Profile in Chronic Renal Failure Patients (Ibrahim Cardiac Medical Journal, 2012)
Background & objective: Chronic Renal Failure (CRF) is a serious condition with a worldwide impact. Anemia is a common complication of CRF leading to significant morbidity. Iron deficiency may be a contributing factor for developing anemia in CRF patients. It may be particularly problematic during erythropoietin therapy. This study was intended to find the serum iron status in CRF patients.Method: This cross sectional study was conducted on 100 consecutive patients of CRF in the Department of Medicine, Rangpur Medical College & Hospital, Rangpur and Hypertension & Research Centre, Rangpur between July 2010 to June 2012.Result: 40% of the patients were 40-59 years old, 28% were 20 - 39 years and 32% >60 years old. Males were predominant (64%) than the females (36%). None of the biochemical variables (serum creatinine, haemoglobin and serum iron profile), except total iron binding capacity (TIBC) differ by sex. TIBC was significantly higher in females than that males (p = 0.029). Of the 100 patients 40% were iron deficient; of them 12(30%) had absolute iron deficiency and 28(70%) relative iron deficiency. Iron deficiency was not influenced by sex (p = 0.519). It was not even affected by the degree of renal insufficiency (p = 0.524). However, the incidence of severe anemia increases significantly with the degree of renal insufficiency (p = 0.037).Conclusion: Serum iron profile remains normal in most of the cases of CRF patients. It should be investigated in every CRF patients before deciding for iron therapy.Ibrahim Cardiac Med J 2012; 2(2): 8-13